ألفاظ الطعام وصفاته في كتاب ))البارع في اللغة(( لأبي علي إسماعيل بن القاسم القالي البغدادي المتوفي سنه) 653 هـ( (Journal of the College of Basic Education, 2023)
1 Why study the book (Al-Bari’ in the Language)?A- We studied at the doctoral level in our dissertation entitled (The social curve of ArabicThrough Lisan al-Arab (by Ibn Manzoor) (d. 711 AH) in the third topic: From the expressions of human foodand mustache) are part of the terms for food and drink that are listed in the dictionary of the Arabic tongue, that encyclopediacomprehensive and timeless linguistics. After these words are an important part of the aspects of the social aspect of the language.Arabic, continuing the same approach and completing the enumeration of food terms and their recipes in a heritage book.Another important point is that we have chosen the book “The Brilliant in Language” by Abu Ali Ismail bin Al-Qasim Al-Qali.Al-Baghdadi, who died in the year 356 AH), investigated by the late Professor Hashim Al-Ta’an to quote his wordsHe wrote it carefully and turned its pages with interest in search of the words of food and its recipes in it to explainIts quality, characteristics and importance in human life and language in the Arab environment. Note that the bookAt the origin of its realization is a scientific thesis that is scientifically served and whose vocabulary can be reassured and achieved.The aforementioned researcher submitted it to the College of Arts and the College of Postgraduate Studies at the University of Baghdad as part ofObtaining a master's degree in the Arabic language in April 1972 AD. The thesis was prepared under the supervision ofThe late Dr. Ibrahim Ahmed Al-Samarei, and its discussion committee consisted of the distinguished professors:* The late Professor Mahdi Al-Makhzoumi* The late Professor Abdul Hamid Al-Ardhi* The late Prof. Dr. Ibrahim Ahmed Al-Samarei (May God perfume all their fruits).The aforementioned committee, the late Ta’an, obtained a master’s degree (with distinction), then the thesis was issued afterThis is in a separate book that the University of Baghdad helped to publish, the addition number (4) in the academic year.1974-1973, and the first edition of it appeared in 1975 from Al-Nahda Library in Baghdad.The House of Arab Civilization in Beirut.